Survival‐Assured Liver Injury Preconditioning (SALIC) Enables Robust Expansion of Human Hepatocytes in Fah–/–Rag2–/–IL2rg–/– Rats - Ludi Zhang; Jian‐Yun Ge; Yun‐Wen Zheng; Zhen Sun; Chenhua Wang; Zhaoliang Peng; Baihua Wu; Mei Fang; Kinji Furuya; Xiaolong Ma; Yanjiao Shao; Nobuhiro Ohkohchi; et al. (Advanced Science, 2021)
Abstract Although liver‐humanized animals are desirable tools for drug development and expansion of human hepatocytes in large quantities, their development is restricted to mice. In animals larger than mice, a precondition for efficient liver humanization remains preliminary because of different xeno‐repopulation kinetics in livers of larger sizes. Since rats are ten times larger than mice and widely used in pharmacological studies, liver‐humanized rats are more preferable. Here, Fah–/–Rag2–/–IL2rg–/– (FRG) rats are generated by CRISPR/Cas9, showing accelerated liver failure and lagged liver xeno‐repopulation compared to FRG mice. A survival‐assured liver injury preconditioning (SALIC) protocol, which consists of retrorsine pretreatment and cycling 2‐(2‐nitro‐4‐trifluoromethylbenzoyl)‐1,3‐cyclohexanedione (NTBC) administration by defined concentrations and time intervals, is developed to reduce the mortality of FRG rats and induce a regenerative microenvironment for xeno‐repopulation. Human hepatocyte repopulation is boosted to 31 ± 4% in rat livers at 7 months after transplantation, equivalent to approximately a 1200‐fold expansion. Human liver features of transcriptome and zonation are reproduced in humanized rats. Remarkably, they provide sufficient samples for the pharmacokinetic profiling of human‐specific metabolites. This model is thus preferred for pharmacological studies and human hepatocyte production. SALIC may also be informative to hepatocyte transplantation in other large‐sized species.